Differentiated Learning Training for Elementary School Teachers as An Implementation of The Merdeka Curriculum - Moh. Rikza Muqtada; Afi Normawati; Muhammad Irvan Ardianto (TAAWUN, 2025)
This community service activity aims to provide differentiated learning training for elementary school teachers in Magelang Regency as an implementation of the Merdeka Curriculum. This curriculum requires educators to provide learning that is tailored to the needs, interests and abilities of students. Partners in this activity are 32 teachers from SDN 1 Payaman and SDN Madusari. Most teachers do not understand in depth the concept of learning. The activity method consists of three main stages, namely preparation, implementation and evaluation. In the preparation stage, the team first analyzes training needs by conducting interviews with teachers. Then, at the implementation stage, activities include delivering material on the basics of differentiated learning, group discussions and micro-teaching practices. The evaluation results showed an increase in the average score from 43.33 on the pretest to 81.90 on the posttest. This training makes a positive contribution in preparing teachers to implement differentiated learning according to students' interests and needs so that students can develop competencies according to expectations.